Principles of deglutition a multidisciplinary text for swallowing and its disorders - Shaker, Reza. (Springer, 2013)
Principles of Deglutition is the first in class comprehensive multidisciplinary textbook to encompass the entire field of normal and disordered deglutition. It is designed as the definitive text for all those who desire to further their knowledge of the dynamic and expanding field of deglutology. The text is created to serve as a treasured reference for clinicians, educators and trainees from such diverse backgrounds as gastroenterology, speech language pathology, otolaryngology, rehabilitation medicine, radiology and others. Principles of Deglutition brings together the state-of-knowledge from 12 disciplines involved in dysphagia through contributions of over one hundred thought leaders and master clinicians for the benefit of patients and providers alike. It concisely organizes the wealth of knowledge that exists in each of the contributing disciplines into one comprehensive information platform. Principles of Deglutition provides a one-stop destination for members of all specialties to obtain state-of-the-art and critically reviewed information regarding deglutition physiology, pathophysiology, diagnosis and management. It delivers a comprehensive and in depth review of deglutition related cerebral cortical, brainstem, peripheral nerves, and neuromuscular mechanisms, advanced diagnostic modalities and standard of care and cutting edge medical, rehabilitative and surgical treatments. It is an essential reference for all deglutologists. Overview of deglutition and digestion -- Gustation, olfaction and deglutition -- Coordination of deglution and respiration -- Airway protective mechanisms, reciprocal physiology of the deglutitive axis -- Cerebral cortical control of deglutition -- Brainstem control of deglutition: swallowing pattern generator -- Brainstem control of deglutition: brainstem neural circuits and mediators regulation swallowing -- Oral phase preparation and propulsion: anatomy, physiology, pheology, mastication and transport -- Deglutitive oral pressure phenomena -- Effect of aging on the oral phase of deglutition -- Nascent oral phase -- Development, anatomy and physiology of the Pharynx -- Development, Anatomy and Physiology of the Larynx -- Development, Anatomy and Physiology of the lungs -- Effect of aging of the pharynx and the UES -- Nascent pharynx, physiology, reflexes -- Development, Anatomy and physiology of the upper esophageal sphincter and pharyngo-esophageal junction -- Deglutitive pharyngeal and UES pressure phenomena -- Development, anatomy and physiology of the esophagus -- Normal aging and the esophagus -- Nascent esophagus, sensory-motor physiology during maturation -- Esophageal motor physiology -- Sphincter mechanisms at the esophago-gastric junction -- Motility and pressure phenomena of the esophagus -- Symptom indices for dysphagia assessment and management -- Cerebro-vascular accidents and dysphagia -- Progressive neurologic disease and dysphagia (include parkinson's disease, multiple sclerosis, amyotrophic lateral sclerosis, myasthenia gravis, post polio syndrome) -- Disorders of appetite, eating and swallowing in the dementias -- Dystrophies and myopathies (to include muscular, oculopharyngeal) -- Dysphagia secondary to the effects of chemo and radiation therapy -- Swallowing syncope -- Globus pharyngeus -- Deglutition in patients with tracheostomy, nasogastric tubes and orogoastric tubes -- Dysphagia secondary to systemic diseases -- -- Cricopharyngeal bar -- Cricopharyngeal achalasia -- UES opening muscle dysfunction -- Achalasia and ineffective esophageal motility -- Esophaegeal spasm/non-cardiac chest pain Hypertensive esophageal peristalsis (nutcracker esophagus) hypertensive lower esophageal sphincter -- Benign and malignant tumors of the esophagus -- Strictures, rings, webs (peptic, caustic, radiation, anastomotic) -- Esophageal foreign bodies: food impaction & foreign bodies -- Post surgical dysphagia: post-nissen fundoplication, C-spine surgery, thyroid surgery, gastric banding, gastric bypass -- Drug-induced esophageal injury -- Inectious esophagitis -- Gastroesophageal reflux disease -- Barrett's esophagus -- Extraesophageal manifestations of reflex disease and dysphagia -- Hiatal hernia -- Psychogenic dysphagia -- Rumination syndrome -- Compensatory management and treatment in dysphagia -- Rehabilitative treatments -- Electrical stimulation treatment -- Pharmacotherapy of UES spastic disorder -- Open and endoscopic cricopharyngeal myotomy -- Surgical treatment of Zenker's diverticulum -- Dilatations (UES, esophagus, LES) Balloon dilations, bougies -- Esophageal stenting for relief of dysphagia -- Botulinum toxin for LES spastic disorders -- Surgical treatment of achalasia and spastic esophageal disorders -- Vocal fold medialization, arytenoid adduction, and partial pharyngectomy -- Laryngohyoid suspension -- Surgical managment of life-threatening aspiration -- Anti-reflux surgery -- Tube feeding: indications, considerations and technique.